Transient blood–brain barrier disruption is induced by low pulsed electrical fields in vitro: an analysis of permeability and trans-endothelial electric resistivity. (1st January 2019) - Sharabi, Shirley; Bresler, Yael; Ravid, Orly; Shemesh, Chen; Atrakchi, Dana; Schnaider-Beeri, Michal; Gosselet, Fabien; Dehouck, Lucie; Last, David; Guez, David; Daniels, Dianne; Mardor, Yael; et al.
Abstract: The blood–brain barrier (BBB) is limiting transcellular and paracellular movement of molecules and cells, controls molecular traffic, and keeps out toxins. However, this protective function is the major hurdle for treating brain diseases such as brain tumors, Parkinson's disease, Alzheimer's disease, etc. It was previously demonstrated that high pulsed electrical fields (PEFs) can disrupt the BBB by inducing electroporation (EP) which increases the permeability of the transcellular route. Our goal was to study the effects of low PEFs, well below the threshold of EP on the integrity and function of the BBB. Ten low voltage pulses (5–100 V) were applied to a human in vitro BBB model. Changes in permeability to small molecules (NaF) were studied as well as changes in impedance spectrum and trans-endothelial electric resistivity. Viability and EP were evaluated by Presto-Blue and endogenous Lactate dehydrogenase release assays. The effect on tight junction and adherent junction protein was also studied. The results of low voltage experiments were compared to high voltage experiments (200–1400 V). A significant increase in permeability was found at voltages as low as 10 V despite EP only occurring from 100 V. The changes in permeability as a function of applied voltage were fitted to an inverse-exponential function, suggesting a plateau effect. Staining of VE-cadherin showed specific changes in protein expression. The results indicate that low PEFs can transiently disrupt the BBB by affecting the paracellular route, although the mechanism remains unclear.